Application of radial GRAPPA techniques to single‐ and multislice dynamic speech MRI using a 16‐channel neurovascular coil. Issue 3 (24th April 2019) - Ruthven, Matthieu; Freitas, Andreia C.; Boubertakh, Redha; Miquel, Marc E.
Abstract : Purpose: To investigate: (1) the feasibility of using through‐time radial GeneRalized Autocalibrating Partially Parallel Acquisitions (rGRAPPA) and hybrid radial GRAPPA (h‐rGRAPPA) in single‐ and multislice dynamic speech MRI; (2) whether single‐slice dynamic speech MRI at a rate of 15 frames per second (fps) or higher and with adequate image quality can be achieved using these radial GRAPPA techniques. Methods: Seven healthy adult volunteers were imaged at 3T using a 16‐channel neurovascular coil and 2 spoiled gradient echo sequences (radial trajectory, field of view = 192 × 192 mm 2, acquired pixel size = 2.4 × 2.4 mm 2 ). One sequence imaged a single slice at 16.8 fps, the other imaged 2 interleaved slices at 7.8 fps per slice. Image sets were reconstructed using rGRAPPA and h‐rGRAPPA, and their image quality was compared using the root mean square error, structural similarity index, and visual assessments. Results: Image quality deteriorated when fewer than 170 calibration frames were used in the rGRAPPA reconstruction. rGRAPPA image sets demonstrated: (1) in 97% of cases, a similar image quality to h‐rGRAPPA image sets reconstructed using a k‐space segment size of 4, (2) in 98% of cases, a better image quality than h‐rGRAPPA image sets reconstructed using a k‐space segment size of 32. Conclusion: This study confirmed: (1) the feasibility of using rGRAPPA and h‐rGRAPPA in single‐ and multislice dynamic speech MRI, (2) that single‐slice speech imaging at a frame rate higher than 15 fps and with adequate image quality can be achieved using these radial GRAPPA techniques.